The Regulation of Intestinal Inflammation and Cancer Development by Type 2 Immune Responses - Gamez-Belmonte, Reyes; Erkert, Lena; Wirtz, Stefan; Becker, Christoph (International Journal of Molecular Sciences, 2020)
The gut is among the most complex organs of the human body. It has to exert several functions including food and water absorption while setting up an efficient barrier to the outside world. Dysfunction of the gut can be life-threatening. Diseases of the gastrointestinal tract such as inflammatory bowel disease, infections, or colorectal cancer, therefore, pose substantial challenges to clinical care. The intestinal epithelium plays an important role in intestinal disease development. It not only establishes an important barrier against the gut lumen but also constantly signals information about the gut lumen and its composition to immune cells in the bowel wall. Such signaling across the epithelial barrier also occurs in the other direction. Intestinal epithelial cells respond to cytokines and other mediators of immune cells in the lamina propria and shape the microbial community within the gut by producing various antimicrobial peptides. Thus, the epithelium can be considered as an interpreter between the microbiota and the mucosal immune system, safeguarding and moderating communication to the benefit of the host. Type 2 immune responses play important roles in immune-epithelial communication. They contribute to gut tissue homeostasis and protect the host against infections with helminths. However, they are also involved in pathogenic pathways in inflammatory bowel disease and colorectal cancer. The current review provides an overview of current concepts regarding type 2 immune responses in intestinal physiology and pathophysiology.
CRIS-Team WoS Importer:2021-01-15